Development of Web-Based Library System at SMP Negeri 3 Sungai Kakap - Lesmana, Chandra; Santoso, Danar; Mannanan, Darul Lutfi (STKIP Singkawang, 2025)
This research aims to develop a web-based library information system at SMP Negeri 3 Sungai Kakap to improve the efficiency of library management and support students' access to learning resources. The research method used was Research and Development (R&D) with the Richey and Klein model, including planning, production, and evaluation stages. The development of the system involved 2 media experts, 3 librarians, and 30 students as respondents. The validation results showed that this system was very feasible, with an average score of 89% from media experts and 88% from expert librarians. The student response was also positive, with a score of 86.13%, indicating satisfaction with the ease of use and benefits of the system. Thus, this web-based library information system was effective in improving library services and supporting the learning process in schools.